Assessing visual function in children with complex disabilities: the Bradford visual function box. Issue 8 (1st December 2015) - Pilling, Rachel F; Outhwaite, Louise; Bruce, Alison
Abstract : Background: Assessment of children with complex and severe learning disabilities is challenging and the children may not respond to the monochrome stimuli of traditional tests. The International Association of Scientific Studies on Intellectual Disability recommends that visual function assessment in poorly or non-cooperative children should be undertaken in an objective manner. We have developed a functional visual assessment tool to assess vision in children with complex and multiple disabilities. Methods: The Bradford visual function box (BVFB) comprises a selection of items (small toys) of different size and colour, which are presented to the child and the response observed. The aim of this study is to establish its intertester validity in children with severe learning disability. The visual function of 22 children with severe learning disability was assessed using the BVFB. The children were assessed by experienced practitioners on two separate occasions. The assessors were unaware of each other's findings. Results: In 15/22 of the children, no difference was found in the results of the two assessors. The test was shown to have a good intertester agreement, weighted κ=0.768. Conclusions: The results of this clinical study show that the BVFB is a reliable tool for assessing the visual function in children with severe learning disability in whom other tests fail to elicit a response. The need for a tool which is quick to administer and portable has previously been highlighted. The BVFB offers an option for children for whom other formal tests are unsuccessful in eliciting a response.